Fort Solitude - Fridolf,s Derek; Dustin Nguyen (New York, N.Y. : Scholastic Inc, 2017)
Congratulations! Your recent academic scoring has placed you in the top of your class. This qualifies you for a week-long evergreen adventure camp!
DC Comics.